Opportunistic Fungal Infection in HIV Positive Patients Attending a Tertiary care Hospital in Eastern Nepal - Sah, Rinku; Gurung, R.; Poudyal, N.; Baral, R.; Rijal, S.; Bhattacharya, S.K. (Journal of BP Koirala Institute of Health Sciences, 2018)
Background: HIV infection continues to be a major health problem with more than millions of AIDS related death annually. The risk of opportunistic infections increases with the depletion of CD4+ count in HIV positive patients which are responsible for the high mortality and morbidity. The spectrum of opportunistic infection (OIs) varies from one region to another. This study was carried out to see the occurrence of opportunistic fungal infection among the HIV positive patients in Eastern Nepal. Method: This was a hospital based descriptive study carried out in Microbiology laboratory, BPKIHS, Dharan, Nepal over a period of one year (15th May 2013 to 14th May 2014). Total 60 HIV positive patients with CD4+ count ≤200 cells/mm3 and suspected of having fungal infections were included. Samples were collected after taking an informed written consent from the patient. Isolation and identification was done as per standard Microbiological procedure. Result: Opportunistic fungal infection was identified in 51.66% patients. The most common fungi isolated were Candida species, Cryptococcus neoformans, Aspergillus species and Dermatophytes respectively being 33.3% (n= 20), 10% (n= 6), 3.3% (n= 2) and 8.3% (n= 5). Candida species comprised 60%, Cryptococcus neoformans 20%, Aspergillus species 5.7% and dermatophytes 14.3% of total fungal isolates. Conclusion: The common fungus isolated were Candida species, Cryptococcus neoformans, Aspergillus species and Dermatophytes in HIV positive patients in this hospital of Eastern Nepal.